Irritating effects on man of air pollution due to cigarette smoke - Weber, A; Jermini, C; Grandjean, E (American journal of public health (1971), 1976)
Sixty subjects were exposed to cigaretts smoke produced by a smoking machine in a climatic chamber. The irritating effects were recorded by questionnaire and related to concentrations of CO, formaldehyde, and acroleine. The eyes are most sensitive to these irritants, followed by the nose. Annoyance about air quality, and the desire to open the window or to leave the room proved to be other useful measures of sensitivity. With smoke produced by 10 cigarettes/30 m3 acroleine reaches 0.1 ppm, the threshold limit value for industries; simultaneously, CO and formaldehyde exceed the clean air standards for outdoor air. At this exposure level. 9 per cent of the subjects show a strong or very strong eye irritation, while 78 per cent "wish to leave the room." The most important of the measured irritants seems to be acroleine.